TIPOLOGI RUANG INTERAKSI DI PERMUKIMAN NELAYAN TAMBAK LOROK KOTA SEMARANG - ramandhika, mirza (Civil Infrastructure Engineering and Architectural Design, 2019)
Settlement as a container for community activities to settle there are 2 primary physical elements, namely the Solid element (building) and the Void element (open space). Public open space as a void element is a space that is not built up in an area of the city that is functioned for the aesthetics and welfare of its citizens, public open space must have a responsive, democratic, and meaningful character. The study was conducted based on the Qualitative paradigm with the main search technique was field observation, a theory which, supporting this research, was used as background knowledge. To find out the typology of the interaction space, an overall observation was carried out to divide the research area large enough into small units to simplify the process of research analysis. The location of the study, namely the Tambak Lorok Fishermen Settlement City of Semarang, at the overall observation stage found differences in the livelihoods of the population, increasingly in the middle of the settlements dominated by fishermen. Interaction space is influenced by physical and non-physical aspects, physical aspects related to the physical condition of the research area, non-physical aspects related to the social culture of the community. The research area is divided into 3 observation units, the TPI area, the Mooring Pier area, and the large mosque area. Differences in physical and non- physical aspects are believed to produce different typologies of interaction space. The determination of aspects of typological analysis is carried out by analysis based on findings in the field.rmukiman sebagai wadah dari kegiatan masyarakat untuk bermukim terdapat 2 elemen fisik primer, yaitu elemen Solid (bangunan) dan elemen Void (ruang terbuka). Ruang terbuka public sebagai elemen void merupakan ruang yang tidak terbangun dalam suatu area kota yang difungsikan untuk estetika, dan kesejahteraan warganya, ruang terbuka public harus memiliki karakter responsif, demokratis, dan bermakna. Penelitian dilakukan berdasarkan pada paradigma Kualitatif dengan teknik pencarian utama adalah observasi lapangan, teori yang ,mendukung penelitian ini digunakan sebagai background knowledge. Untuk mengetahui tipologi ruang interaksi dilakukan observasi keseluruhan untuk membagi daerah penelitian yang cukup besar menjadi unit kecil untuk mempermudah proses analisis penelitian. Lokasi penelitian, yaitu Permukiman Nelayan Tambak Lorok Kota Semarang, pada tahap observasi keseluruhan menemukan perbedaan mata pencaharian penduduk, semakin ke tengah permukiman didominasi oleh nelayan. Ruang interaksi dipengaruhi oleh aspek fisik dan non fisik, aspek fisik berkaitan dengan keadaan fisik area penelitian, aspek non fisik berkaitan dengan sosial budaya masyarakat. Area penelitian terbagi menjadi 3 unit amatan, area TPI, area Dermaga Tambat, dan area masjid besar. Perbedaan aspek fisik dan non fisik diyakini menghasilkan tipologi ruang interaksi yang berbeda. Penentuan aspek analisis tipologi dilakukan dengan analisis yang dilakukan berdasarkan temuan di lapangan.